Implementasi Kebijakan Analisis Jabatan dan Beban Kerja pada Sekretariat Jenderal - Kartika, Enggaria Ratna Dewi; Budiharjo, Budiharjo; Nenobais, Harry (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the implementation of job analysis and workload analysis policies at the Secretariat General of the Ministry of Home Affairs and to identify key challenges and improvement strategies. The analytical framework is based on Edward Gerston’s policy implementation theory, which includes policy translation capacity, resource availability, limited number of implementers, and accountability. A qualitative descriptive approach was employed, with data collected through participant observation, in-depth interviews, document analysis, and literature review. Informants were selected using purposive sampling, involving 12 individuals with in-depth knowledge of the policy implementation process. Data analysis followed the stages of data collection, data reduction, data display, and conclusion drawing. The findings indicate that the implementation of job analysis and workload analysis policies has not been optimal. This condition is reflected in limited knowledge and competence among policy implementers, an insufficient number of implementers, and the absence of a formally established and continuously operating implementation team. Recommended improvement efforts include strengthening competency development and training programs, expanding the use of flexible e-learning systems, establishing a permanent implementation team through ministerial decrees on an annual basis, and developing comprehensive standard operating procedures covering all units within the Ministry of Home Affairs.